شهود الأحدية عند ابن عطاء الله؛ مفهومها ولواحقها ودورها في تأسيس ميتافيزيقا العلوم الكونية - Moh Isom Mudin (Universitas Darussalam Gontor, 2018)
This paper will analyse the concept of “Syuhûd al-Aḥadiyah” according to Ibn Athaillah al-Sakandary and its urgency as a basic assumption of Islamic science. The background of this paper starts from a problem of modern western science which is not value-free as it holds metaphysical assumptions that are not suitable with Islamic worldview. The author will use the philosophical approach of SMN. al-Attas, that he offers the structure of Sufi`s metaphysics as a basis for Islamic science. Then, “Syuhûd al-Aḥadiyah” can replace the metaphysical structure of modern science. According to Ibn Athaillah, the Sufis who have reached the degree of makrifat will witness to the absolute oneness of Allah SWT, and it will have implications for the view of reality, both absolute reality that God has, and the relative reality that nature has. This nature comes from nothing, and then it exists through the ‘îjâd’ process. Furthermore, it also exists by the ‘intervention of God’, namely ‘imdâd’ process. This nature is also a manifestation of God’s attributes. This Sufi metaphysical view is very important to be used as a part of the basic assumption of Islamic science vis a vis modern science that it views the nature as independent, eternal, self-governing, and has no relation to reality or it considered as the only reality. This assumption has its implications for the positive method which considers experimentation as the only method of attaining the truth. Therefore, the discussion of the relationship of “Syuhûd al-Ah adiyah” finds its urgency as the basic assumption of Islamic science.